Top-down fabrication of α-Fe2O3 single-crystal nanodiscs and microparticles with tunable porosity for largely improved lithium storage properties - Chen, Jun Song (2012)
In this work, we report a facile top-down approach to fabricate uniform single-crystal α-Fe2O3 nanodiscs via selective oxalic acid etching. Phosphate ions are employed as a capping agent to control the etching to along the [001] direction. We also show that α-Fe2O3 melon-like microparticles with contrasting textural properties can be generated using the same approach. The etched particles exhibit a much larger total pore volume and average pore size compared to the pristine ones, thus serving as the possible origin for their greatly enhanced capacity retention when tested as potential anode materials for lithium-ion batteries.